Sistem Monitoring RPM Roda Smart Wheelchair Pada Halaman Web Berbasis Ajax Menggunakan Sensor Optocoupler - Afdy Clinton; Dahnial Syauqy; Fitri Utaminingrum (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The difference in the speed of an electric motor can produce an unsuitable output. The use of two electric motors with different speeds to move the wheels of a smart wheelchair or a robot car causes the device to move in the direction that is not intended. Based on these problems, it needs a wireless RPM monitoring system in order to know the speed difference between the two motors or both wheels with ease. This study focuses on knowing the RPM of both wheels smart wheelchair by using incremental encoder. 2 Optocoupler Sensors and 2 encoder disks with 20holes is implemented in the smart wheelchair to know the RPM value of each wheel. The Optocoupler sensor is used to detect how many holes are detected in 1sec, so the RPM of the motor or wheel can be known. Based 50 tests ​​of the Optocoupler Sensor on the right side of the prototype obtained an average percent error of 0.92% and the left side obtained 0.87%. Based on 10 tests of Sensor Optocoupler on the right side on smart wheelchair obtained an average percent error of 2.00% and left side obtained 2.06%. The connection status of NodeMCU WiFi when connected to a laptop at a distance of 10-50meter is connected and the connection status at a distance of 60-70meter is disconnected.